The Legal Vacuum of Time Limits for the Resolution of Judicial Review Cases in the Constitutional Court from the Perspective of Siyasah Dusturiyah - Muhammad Imam Syuhada; Muhammad Syuib; Bustamam Usman (Teunuleh Publisher, 2026)
This study highlights the issue of a regulatory void within the procedural law of the Constitutional Court, specifically regarding the absence of a time limit for the settlement of judicial review cases. Unlike election dispute cases which have strict statutory deadlines, judicial review proceedings often experience undue delays. This research aims to analyze the legal implications of this norm vacuum and formulate an ideal case settlement concept through the perspective of Siyasah Dusturiyah. The method employed is juridical-normative with statutory and conceptual approaches. The findings indicate that the absence of a time limit in Law Number 7 of 2020 creates legal uncertainty, which contravenes the principle of a speedy trial (contante justitie). From the perspective of Siyasah Dusturiyah, this condition violates the principles of Al-‘Adl (justice) and ‘Adam al-Ta’khir (prohibition of delaying rights) within the judicial power (Wilayatul Qadha). Therefore, a reconstruction of regulations establishing a maximum duration for case settlement is necessary for the benefit of justice seekers. Penelitian ini menyoroti persoalan kekosongan norma dalam hukum acara Mahkamah Konstitusi, khususnya terkait ketiadaan pengaturan batas waktu penyelesaian perkara pengujian undang-undang (judicial review). Berbeda dengan sengketa hasil pemilihan umum yang memiliki tenggat waktu limitatif, perkara uji materi seringkali mengalami proses peradilan yang berlarut-larut (undue delay). Penelitian ini bertujuan menganalisis implikasi hukum dari kekosongan norma tersebut serta merumuskan konsep penyelesaian perkara yang ideal melalui kacamata Siyasah Dusturiyah. Metode yang digunakan adalah yuridis-normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa ketiadaan batas waktu dalam Undang-Undang Nomor 7 Tahun 2020 menciptakan ketidakpastian hukum yang bertentangan dengan asas peradilan cepat (contante justitie). Dalam perspektif Siyasah Dusturiyah, kondisi ini melanggar prinsip Al-‘Adl (keadilan) dan ‘Adam al-Ta’khir (larangan menunda hak) dalam kekuasaan kehakiman (Wilayatul Qadha). Oleh karena itu, diperlukan rekonstruksi regulasi yang menetapkan durasi maksimal penyelesaian perkara demi kemaslahatan pencari keadilan.